Essential medicines for pediatric oncology in developing countries1. Issue 5 (28th February 2013) - Mehta, Parth S.; Wiernikowski, John T.; Petrilli, J A. Sergio; Barr, Ronald D.; ,
Abstract The burden of cancer in children in low and middle income countries (LMICs) is substantial, comprising at least 80% of incident cases globally, and an even higher proportion of cancer‐related deaths. With survival rates exceeding 80% in high income countries, it is imperative to transfer these successes to LMICs. A major challenge is the poor availability of safe, cost‐effective chemotherapy. A list of 51 drugs—chemotherapeutics, infectious disease agents, and supportive care medications—is proposed as essential to improving the survival of children with cancer in LMICs with an additional 13 drugs identified as being of further value. Pediatr Blood Cancer 2013; 60: 889–891. © 2013 Wiley Periodicals, Inc.